Antimicrobial and Cytotoxic Potential of the Compound Secreted by Marine Bacteria Collected from the Karwar Coast, West Coast of India - Pradeep V. Khajure; J. L. Rathod (Universitas Gadjah Mada, 2011)
Antibacterial substances from sea sediment were isolated from marine environment of Karrwar, westcoast of India and characterized. Out of the 21 isolates subjected to secondary screening, 10 isolates were activeagainst Bacillus subtilis, 12 against Staphylococcus aureus, 6 against Escherichia coli, 3 against Proteus vulgaris and4 against Salmonella typhi. Metabolites in the broth extract of overnight grown Pseudomonas spp. No.7 provedto have antimicrobial and cytotoxic against human lung carcinoma cell